Monetary and Fiscal Policy Interaction in the EMU: A Dynamic Game Approach - Bas van Aarle; Jacob Engwerda; Joseph Plasmans (Center for Economic Studies and ifo Institute (CESifo), 2001)
The interaction of monetary and fiscal policies is a crucial issue in a highly integrated economic area as the European Union. We argue that EMU, which introduced a common monetary policy and restrictions on fiscal policy at the national level, increases the need for macroeconomic policy cooperation. To study the effects of policy cooperation we compare the effects of three alternative policy regimes in a stylized dynamic model of a monetary union: (i) noncooperative monetary and fiscal policies, (ii) partial cooperation, and (iii) full cooperation both in symmetric and asymmetric settings where countries differ in structural characteristics, policy preferences and/or bargaining power. The paper introduces an analysis of coalitional behavior in a dynamic setting into the literature.
Keywords: 330